Pre- and perinatal risk factors for child maltreatment in military families across the first two years of life - Sullivan, Kathrine S. (Child maltreatment, 2023)
Military families are exposed to a unique constellation of risk factors, which may impact maltreatment outcomes. The present study examined prospective relationships between demographic, health, birth-related, and military-specific risk factors identified prior to a child?s birth on their risk for maltreatment in the first two years of life. Data from the Millennium Cohort Study, Department of Defense (DoD) operational records and Family Advocacy Program data on met-criteria maltreatment, and Birth and Infant Health Research program data on suspected maltreatment were linked for 9076 service member parents. Discrete time survival analysis showed that preterm birth increased risk of maltreatment while parents? older age, physical health, and service in the Navy or Air Force decreased risk. Building on DoD?s New Parent Support Program, findings suggest the need for universal and targeted prevention efforts, beginning during pregnancy, which limit or eliminate risk factors for maltreatment in military families.